Criminal Legal Analysis on Conversion of Forest Areas Into Oil Palm Plantations: A Case Study in Belitung Regency - Yuda, Darma; Sukrisno, Wijayono Hadi (Jurnal Daulat Hukum, 2025)
This study aims to analyze the crime of converting forest areas into oil palm plantations in Belitung Regency. The focus of the study is directed at the identification of elements of criminal acts in the misuse of forest areas as well as the application of criminal law and forestry administration in the settlement of these cases. The research method used is normative juridical with a legislative approach and case studies. The results of the study show that the conversion of forest areas without permits violates the provisions of Law Number 41 of 1999 concerning Forestry and Law Number 18 of 2013 concerning the Prevention and Eradication of Forest Destruction. Elements of criminal acts include unlawful acts, environmental damage, and intentional elements. The application of criminal law has not been maximized due to weak supervision, lack of coordination between agencies, and lack of deterrent effect for perpetrators. Meanwhile, from the aspect of forestry administration, the control of permits and the restoration of forest areas are important steps in the effort to solve it. A more stringent legal approach and improved forest governance are needed to prevent the recurrence of similar violations in the future.